Surface topography of Dome Concordia (Antarctica) from kinematic interferential GPS and bedrock topography - CAPRA, Alessandro; R. Cefalo; S. gandolfi; G. Manzoni; I. E. Tabacco; L. Vittuari (Annals of Glaciology, 2000)
Determination of surface topograpghy of Dome C area, Anatrtica. Generation of the DTM of the area with GPS kinematic method: data and results analysis.